Channel impulse response equalization based on genetic algorithm in mode division multiplexing - Fareed, Alaa; Amphawan, Angela; Fazea, Yousef; Sajat, Mohd Samsu; Chit, Suwannit Chareen (Universiti Teknikal Malaysia Melaka, 2018)
This paper proposed to use genetic algorithm (GA) as an adaptive algorithm for mode division multiplexing (MDM) equalization in order to minimize the mean square error as well as to maximize the similarity between the ideal signal and the MDM distorted signal. A significant result has been obtained of implementing GA on MDM equalization compared to other conventional algorithm such as least mean square (LMS) which is used dominantly in current equalizations.